True nature of hybrid work - Matti Vartiainen; Outi Vanharanta (Frontiers in Organizational Psychology, 2024)
IntroductionThis article reviews the discussion concerning hybrid work (HW) during and after the pandemic. We argue that understanding hybrid work as simply dividing working time between an office and another location limits the potential of organizing work sustainably based on organizations' goals and employee needs. Understanding the core nature of hybridity as a flexible and systemic entity and a “combination of two or more things” impacting work outcomes such as wellbeing and performance opens a much richer view of organizing work now and in the future. The critical questions are: What is the core nature of hybridity when two or more things are combined in work, and what factors influence configuring them? Moreover, what are their potential wellbeing and performance outcomes?MethodsTo discover core elements, we reviewed how the HW concept was defined in consulting companies' publications, business journals, and international organizations' publications, mainly focusing on challenges and opportunities for hybrid work during COVID-19. We also analyzed how the concept was used in European questionnaire findings from 27 EU countries during the pandemic. The potential wellbeing and performance outcomes were studied using a sample of prior literature reviews on remote and telework. To identify “Two or more things” in the discussions, we broke down the HW concepts into the physical, virtual, social, and temporal work elements and their sub-elements and designable features.ResultsWe found that the concepts used in the discussions on hybrid work reflect traditional views of remote and telework as a combination of working at home and in the office.DiscussionWe suggest configuring hybrid work as a flexible entity, which opens a perspective to design and implement diverse types of hybrid work that are much more prosperous and sustainable than just combining onsite and offsite work. The expected wellbeing and performance outcomes can be controversial due to the misfit of the hybrid work elements with the organizational purpose, employee needs and expectations, and non-observed contextual factors in implementations.